Pediatric ENT - Graham, John M.; Scadding, Glenis K.; Bull, Peter D. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
In recent years there has been increasing sub-specialization and a rapid expansion of the range of therapies available to pediatric ENT specialists. This concise, up-to-date textbook deals comprehensively with all the practical and theoretical aspects necessary for those taking exams or wishing to up-date their knowledge. It is divided into sections covering rhinology, otology and head and neck problems. The uniformly structured chapters cover all relevant topics comprehensively and succinctly. The authors are from Europe and the US and are internationally renowned experts in their fields. This useful and reader-friendly textbook will not only be inspirational to young specialists with an interest in pediatric ENT, but also to those who are due to take their final exams as well as for established specialists in the field.